Multifocal versus Monofocal Intraocular Lens: Retrospective Comparative Evaluation of Visual Acuity, Spectacle Dependency and Patient Satisfaction - Saad A. Waheeb (Journal of King Abdulaziz University: Medical Sciences, 2023)
To compare visual outcome, subjective visual experience, and satisfaction between eyes with multifocal intraocular lens and monofocal intraocular lens. This is a retrospective chart review of 39 eyes of 20 patients in Group A, who received multifocal intraocular lens. At 6 months postoperative; uncorrected, best corrected distance visual acuity and near visual acuity were collected. Patients self responses questionnaire on spectacle dependency, visual phenomena and overall satisfaction was considered. Results were compared with those in 40 eyes (20 patients) Group B implanted with the SA60AT monofocal IOL as a control group. Uncorrected distance acuity of 0.7 was achieved in 87.2% eyes in the multifocal group; 90.0% in the monofocal group and of 0.8 or better, in 74.4% and 70.0%, respectively. Best corrected distance acuity of 0.8 was achieved in all eyes in both groups and of 0.9-1.0 in about 95.0% in both groups. The mean postoperative spherical error was + 0.30 diopter in the multifocal group and - 0.14 diopter in the monofocal group. Multifocal intraocular len patients reported reduced dependency upon glasses for all distances. Multifocal group experienced significantly more halos and glare.